Deep Structure of the Antarctic Plate's Boundary Zone Along Mid-Ocean Ridges on the Cross-Sections and Lateral Slices - Greku, R.Kh.; Greku, T.R. (Український антарктичний журнал, 2009)
3D vertical structure of the Antarctic Plate's boundary along longitudinal cross-sections and lateral slices at different depths is displayed through a distribution of density anomalies relative to Preliminary Reference Earth Model (PREM) using the harmonic coefficients of the EGM96 geoid model. Features of interaction between the Antarctic Plate and other plates are shown with our gravimetric tomography data over more than 40,000 km along the palte boundary. Two bodies (plumes) dominate in the mantle. Less dense masses ascend from depth of 2800 km and then split up at the depth of 200 km as three branches to the Australian-Antarctic Discordance (AAD), the Ross Sea and the Nazca plate. Dense masses descend from a surface as subducted slabs and collect at depths of 60 km and 280 km. It was discovered in the AAD area and the Nazca Ridge that thinning hot masses penetrate into the colder crust and lithosphere. В работе рассматриваются вертикальный разрез строения Земли вдоль границы Антарктической плиты, а также карты латеральных сечений распределения плотностных неоднородностей на различных глубинах. Аномалии плотности рассчитаны с использованием гармонических коэффициентов гравитационной модели геоида EGM96. Особенности взаимодействия между Антарктической плитой и другими литосферными плитами на протяжении более чем 40 000 км показаны на ортогональных по отношению к границе разрезах. Два тела (плюмы) доминируют в мантии Антарктического региона. Менее плотные массы поднимаются с глубины 2800 км и затем на глубине 200 км разделяются на три отдельных ветви в районах Австралийско-Антарктического Несогласия (ААН), моря Росса и плиты Наска. Плотные массы погружаются от поверхности как субдукционные плиты и концентрируются на глубинах 60 км и 280 км. Обнаружено, что разуплотнённые разогретые массы проникают в более холодную океаническую кору и литосферу в области ААН и хребта Наска. Co-authors express thanks the co-editor and all reviewers for their significant work to improve this paper. We thank also Dr. Viktor Usenko from the Institute of Geological Science of the National Academy of Science of Ukraine for his discussions of the data. This work was supported by the National Antarctic Scientific Center of Ukraine.